2014
DOI: 10.1083/jcb.201402079
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous remodeling is a driver of failed regeneration in Duchenne muscular dystrophy

Abstract: In Duchenne muscular dystrophy, asynchronous regeneration in microenvironments within muscle tissue results in development of fibrosis in lieu of global muscle recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(196 citation statements)
references
References 60 publications
6
179
0
1
Order By: Relevance
“…The gradual loss of muscle tissue that occurs in patients affected by DMD has been attributed to an impaired regeneration process and to the progressive alteration of stem cell function in response to the chronic stimuli resulting from the constant repair of degenerating muscle fibers [33,34]. Indeed, repeated cycles of muscle degeneration and regeneration are key features of DMD pathology.…”
Section: Continuous Cycles Of Myofiber Degeneration and Regenerationmentioning
confidence: 99%
“…The gradual loss of muscle tissue that occurs in patients affected by DMD has been attributed to an impaired regeneration process and to the progressive alteration of stem cell function in response to the chronic stimuli resulting from the constant repair of degenerating muscle fibers [33,34]. Indeed, repeated cycles of muscle degeneration and regeneration are key features of DMD pathology.…”
Section: Continuous Cycles Of Myofiber Degeneration and Regenerationmentioning
confidence: 99%
“…Indeed, timing plays a crucial role in muscle remodeling. For instance, Dadgar et al (2014) demonstrated that asynchrony drives fibrosis and regeneration failure in the mdx model, finding a link between profound deregulation of global muscle transcription and the muscle damage seen in various dystrophies, including dystrophinopathies and several LGMD types. In addition, BMAL1 has recently been found to be involved in myogenic response to muscle damage, orchestrating the regeneration processes in adult skeletal muscle (Chatterjee et al, 2015).…”
Section: Circadian Genes and Hereditary Myopathies -A New Perspectivementioning
confidence: 99%
“…It appears that CLOCK gene deregulation could provide a link between autophagy, mitochondrial abnormalities and ColVI diseases. In light of the asynchrony recently described as the mechanism driving regeneration failure (Dadgar et al, 2014), this relationship could be expressed as one of the two following scenarios. First, that circadian rhythm deregulation is a downstream effect of ColVI deficiency and contributes to muscle damage pathogenesis (Fig.…”
Section: Putative Models Linking Collagen VI Myopathies With Circadiamentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, une infiltration chronique, ou mal coordonnée, de ces divers types cellulaires peut nuire à la régénération musculaire. Ainsi, des blessures musculaires successives induites par deux injections de notexine 2 séparées de quelques jours, provoquent une régénération musculaire asynchrone, un recrutement leucocytaire chronique et augmentent la fibrose tissulaire [31]. Plusieurs conditions SYNTHÈSE REVUES à long terme, la dysfonction musculaire des souris dystrophiques.…”
Section: Inflammation Et Conditions Pathologiques Ou Chroniquesunclassified